Symptomatic, Alexithymic, and Suicidality-Related Features in Groups of Adolescent Self-Harmers: A Case-Control Study - Alessia Raffagnato; Marina Miscioscia; Rachele Fasolato; Sara Iannattone; Perla Valentini; Eleonora Sale; Michela Gatta (European Journal of Investigation in Health, Psychology and Education, 2023)
Non-suicidal self-injury (NSSI) is an increasing phenomenon among both clinical and nonclinical adolescent groups and is associated with several psychopathological symptoms, in addition to being one of the main risk factors for suicidality. Nevertheless, differences between clinical and nonclinical samples of self-harmers in symptom dimensions, alexithymia, suicidality, and NSSI-related variables are still scarcely investigated. The current study aimed to fill this gap by enrolling a sample of Italian girls (age range: 12–19 years) that included 63 self-harmers admitted to mental health outpatient services (clinical group), 44 self-harmers without admission to mental health services (subclinical group), and 231 individuals without an NSSI history (control group). Questionnaires investigating psychopathological symptoms, alexithymia, and NSSI-related variables were administered. The results highlighted that all symptom-related variables and alexithymic traits were more severe in the NSSI groups than in the control group; in particular, self-depreciation, anxiety, psychoticism, and pathological interpersonal relationships were distinguished between the clinical and subclinical groups. Compared to the subclinical group, the clinical group was characterized by higher NSSI frequency, NSSI disclosure, self-punishment as the main reason for engagement in NSSI, and suicidal ideation. These findings were then discussed in terms of clinical practice and primary and secondary prevention in the adolescent population.